2016
DOI: 10.1590/1980-5373-mr-2015-0641
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cr Additions on Ferrite Recrystallization and Austenite Formation in Dual-Phase Steels Heat Treated in the Intercritical Temperature Range

Abstract: An experimental investigation was conducted using laboratory-processed low carbon Mn-Mo-Nb-Ti-B dual phase steel with additions of 0.2Cr or 0.6%Cr. This study investigates the effect of Cr additions on ferrite recrystallization and austenite formation during continuous annealing in the intercritical temperature range. It was found that moderate additions of Cr (0.2%) accelerates the ferrite recrystallization (nucleation and growth) resulting in coarse ferrite grains. An increase in Cr content up to 0.6% also a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In addition, since Cr is a strong carbide-forming element, Cr has a strong connection with carbon, resulting in difficulties in moving the phase interface. As the above factors are keys aspect of the It can be seen that the grain size of the ferrite of Cr-free steel is large, while the grain size is fine in 0.3Cr steel, as the addition of Cr accelerates the recrystallization of ferrite [21]. As the Cr content increases, the ferrite is subjected to rapid recrystallization and growth during the inter-critical isothermal process.…”
Section: Effect Of Cr On Microstructure Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, since Cr is a strong carbide-forming element, Cr has a strong connection with carbon, resulting in difficulties in moving the phase interface. As the above factors are keys aspect of the It can be seen that the grain size of the ferrite of Cr-free steel is large, while the grain size is fine in 0.3Cr steel, as the addition of Cr accelerates the recrystallization of ferrite [21]. As the Cr content increases, the ferrite is subjected to rapid recrystallization and growth during the inter-critical isothermal process.…”
Section: Effect Of Cr On Microstructure Evaluationmentioning
confidence: 99%
“…Additionally, the grain size and the distribution of local misorientation are examined by EBSD. The inverse pole figure (IPF) color maps corresponding to the microstructure obtained by Process 2 and the arrows pointing to the different phase are shown in Figure 4.It can be seen that the grain size of the ferrite of Cr-free steel is large, while the grain size is fine in 0.3Cr steel, as the addition of Cr accelerates the recrystallization of ferrite[21]. As the Cr content increases, the ferrite is subjected to rapid recrystallization and growth during the inter-critical isothermal process.…”
mentioning
confidence: 99%
“…The nucleation and growth of austenite in steels during the annealing processes have been widely investigated [124,125,[141][142][143][144][145][146][147][148][149][150][151]. It is known that austenitic grain size affected the martensite start temperature [152][153][154].…”
Section: Nucleation and Growth Of New Grainsmentioning
confidence: 99%
“…Moreover, the excessive addition of vanadium had a deteriorative effect on the mechanical properties of UFG-DP steels. Silva Filho et al [142] explored the effects of chromium addition on ferrite recrystallisation and austenite formation during intercritical annealing of DP steels. It was found that addition of moderate chromium content up to 0.2% accelerated the ferrite recrystallisation regarding both nucleation and growth and subsequently resulted in coarse ferrite grains in the final DP microstructure.…”
Section: Alloying Elementsmentioning
confidence: 99%